Theoretical Perspectives on Educational Transformation Modeling: Ethno-Sociological Approaches and Value Strengthening in Futuristic Learning - Moruk, Selviana; Sulisworo, Dwi; Susanti, Ani; Ximenes, Joao (The Indonesian Institute of Science and Technology Research, 2025)
Education plays a crucial role in shaping societal values, particularly in the context of globalization and technological advancements. This study explores the transformation of education through an ethno-sociological approach, emphasizing integrating cultural values into futuristic learning. The research aims to develop a conceptual framework that strengthens local cultural values while adapting to modern educational trends. Using a literature review and conceptual analysis, this study examines key factors influencing education, including social, cultural, and economic aspects, as well as the role of technology in learning. The findings highlight that ethno-sociological education fosters inclusivity, cultural preservation, and social cohesion. The proposed model integrates value-based education with technological advancements, ensuring that learning remains holistic and culturally relevant. However, policy constraints, digital divides, and resistance to change must be addressed to ensure successful implementation. The study recommends a balanced integration of technology and traditional educational values, policy adjustments to support inclusive and value-based learning, and developing teacher training programs incorporating ethno-sociological perspectives. Future research should explore empirical applications of this model to assess its effectiveness in diverse educational settings.